THE SOCIOLINGUISTIC STUDY OF TABOO WORDS IN GRAND THEFT AUTO V PROLOGUE STORY MISSION - Arkaan, Anantio Roofiif (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This research objective is to find out what types of taboo words and function used in the game Grand Theft Auto V. This research use theory based on Battistella’s theory on taboo words types, Wardhaugh’s theory on the function of taboo words and to bridge between types and function using Lyon’s theory on contextual analysis. The researcher found that the character in this game tend to use obscenity (48.57%) on types of taboo words and draw attention (48.57%) as the function of taboo words.